Implementation of the strategy of sustainable development of Ukraine's economy in the context of post-war reconstruction (Economics and region, 2025)
The article discusses the practical principles of implementing a strategy for sustainable development of Ukraine's economy in the context of post-war reconstruction. The study is based on an analysis of macroeconomic indicators, GDP dynamics, and structural changes in key sectors of the economy. It is established that economic recovery requires a comprehensive approach that includes institutional reforms, technological innovation, and environmental sustainability. In particular, creating a favorable investment climate, developing human capital, and improving the efficiency of public administration are important components of the economic strategy. Particular attention is paid to the analysis of changes in the structure of Ukraine's GDP by the production method in actual prices in 2021-2023. It is found that among the priority areas of post-war recovery are the stimulation of the construction industry, the development of logistics systems and integration into global economic processes. It is emphasized that a significant role in economic recovery belongs to the state policy that promotes exports, expansion of the domestic market and harmonization of Ukrainian legislation with European standards. The study showed that the strategy for sustainable development of Ukraine's economy should take into account not only macroeconomic indicators, but also structural changes, investment activity, and the level of integration into the global economic space. Positive trends in key sectors of the economy indicate the possibility of a gradual recovery and lay the groundwork for long-term sustainable development. The author proposes measures to modernize production, develop infrastructure and improve regulatory policy, which are necessary to ensure economic stability and competitiveness of Ukraine in the context of post-war recovery. It is noted that investment activity is a determining factor for the modernization of production facilities and infrastructure restoration. It is emphasized that integration into the European Economic Area requires harmonization of Ukraine's regulatory framework with EU standards.
Keywords: economic development; economic recovery; sustainable development; macroeconomic indicators; global challenges; investments; public policy